Three levels of endodontic treatment in modern Russian Dentistry (discussion article) (LLC "Endo Press", 2020)
We discuss the criterions of quality of endodontic treatment, depending on the material and technical provision and the level of funding of dental clinics. The thesis of the three levels of the endodontic care in modern Russian dentistry is justified. The possible directions for applied research and practical developments aimed at improving the quality and accessibility of endodontic treatment are considered.